The effect of additional protein, phosphatidylcholine, phosphatidylserine, and inulin on S100β levels of acute ischemic stroke patients at Dr. Kariadi Central Hospital, Semarang - Stephani Nesya Renamastika; Endang Mahati; Martha Kartasurya; Dodik Pramukarso; Dwi Pudjonarko; Retnaningsih Retnaningsih (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: The brain releases biochemical substrates, such as S100β protein, into circulation in response to ischemic conditions as a sign of damage in nerve cells and disruption of the blood-brain barrier’s integrity. Thrombolytic therapy has led to the development of many neuroprotective therapies such as protein, phosphatidylcholine, phosphatidylserine, and inulin, which can be added to food products. Protein, phospholipids, and inulin, have a neuroprotective impact on nerve cells in the brain and blood-brain barrier.Objective: To prove the effect of protein, phosphatidylcholine, phosphatidylserine, and inulin on S100β levels and clinical outcomes in patients with acute ischemic stroke.Materials and Methods: This study was done in a single-blind RCT. Eighteen ischemic stroke patients were randomly divided into nine subjects for the intervention group and nine subjects for the control group. The Control group received 250 ml conventional formula milk (11.8 g protein) 3 times/day. The intervention group received 250 mL commercial milk 3 rimes/day which contained 15 g protein with 128 mg phosphatidylcholine, 32 mg phosphatidylserine, and 3 g inulin. All of the groups were given hospital-standard therapy for ischemic stroke. S100β levels were measured at pre and post-intervention.Results: Pre and post S100β levels in intervention and the control group did not show any statistically difference (p = 0.777 and p = 0.096), but there was a trend of decreasing  levels of S100β in the intervention group (-24.6 + 252.0 pg/mL) versus control group (135.8 + 216.2 pg/mL).Conclusions: The addition of protein, phosphatidylcholine, phosphatidylserine, and inulin did not have a significant effect on S100β levels.